Self Confidence and Anxiety of Health Volunteers while Doing First Aid for Accident Victims in Surabaya - Merina Widyastuti; Nur Wulan Adhani Lakato; Nur Muji Astuti; Ninik Ambarsari; Christina Yuliastuti; Imroatul Farida; Sri Anik Rustini (Critical Medical and Surgical Nursing Journal (CMSNJ), 2022)
Introduction: Health volunteers are first aid actors in the field when an accident occurs, health volunteers face various situations and conditions from victims and the environment, so they experience anxiety, the anxiety experienced can be an obstacle to first aid handling. This study aims to identify factors related to the anxiety of health volunteers when performing first aid on accident Methods: This study used an analytic observational design with a cross-sectional approach, the population of this study was the health volunteers of the city of Surabaya, amounting to 220 people. The sampling technique used probability sampling with a simple random sampling approach and obtained 103 respondents according to the inclusion and exclusion criteria. The research instrument was a questionnaire in the form of a google questionnaire consisting of questionnaires for demographic data, anxiety (DASS 42), motivation (VFI), and self-confidence (Lauster). Data analysis using Spearman Rho statistical test with p = 0.05. Result: The results of the study showed that the majority of respondents experienced a very severe level of anxiety (36.9%) and a weak majority level of self-confidence (96.1%). The results of the analysis of the relationship between self-confidence and anxiety levels obtained p = 0.003 (p <0.05). Conclusion: There is a relationship between self-confidence and the level of anxiety of health volunteers.